2021
DOI: 10.1111/clr.13708
|View full text |Cite
|
Sign up to set email alerts
|

Guided bone regeneration of chronic non‐contained bone defects using a volume stable porous block TiO2 scaffold: An experimental in vivo study

Abstract: Objectives To evaluate new lateral bone formation and lateral volume augmentation by guided bone regeneration (GBR) in chronic non‐contained bone defects with the use of a non‐resorbable TiO2‐block. Materials and methods Three buccal bone defects were created in each hemimandible of eight beagle dogs and allowed to heal for 8 weeks before treatment by GBR. Each hemimandible was randomly allocated to 4‐ or 12‐week healing time after GBR, and three intervention groups were assigned by block randomization: TiO2 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 43 publications
3
16
0
Order By: Relevance
“…The results suggest that the TiO 2 scaffolds hold the basic requirements for a bone substitute; osteoconductive, biocompatible, space-making capability and volume maintenance [ 34 ], also confirmed in previous in vivo studies [ 18 , 19 , 31 ]. However, the TiO 2 scaffolds are lacking osteoinductive properties as bone formation is seen only from the lateral borders of the grafts, originating from the parent bone.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The results suggest that the TiO 2 scaffolds hold the basic requirements for a bone substitute; osteoconductive, biocompatible, space-making capability and volume maintenance [ 34 ], also confirmed in previous in vivo studies [ 18 , 19 , 31 ]. However, the TiO 2 scaffolds are lacking osteoinductive properties as bone formation is seen only from the lateral borders of the grafts, originating from the parent bone.…”
Section: Discussionsupporting
confidence: 84%
“…The new bone formation within the porous structures in eleven out of twelve scaffolds may indicate sufficient mechanical stability of the scaffolds for bone healing. Fractured scaffold edges were not found as previously reported [ 31 ]. This can be explained by three-wall defects in the present study, which provide stability and shelters the scaffold from external forces in contrast to its use in lateral bone augmentation models.…”
Section: Discussionsupporting
confidence: 67%
“…TiO2 scaffolds, as used here, show promising results in various in vivo experiments [6,8,11]. However, in a recent study [12] using a chronic non-contained bone defects application, less bone formation was observed in the TiO2 groups compared to membrane alone at the final time point of 12 weeks of healing. To improve the clinical performance of bone scaffolds, various bioreactor systems are suggested, including spinner flasks, rotating wall bioreactors, and perfusion systems [21].…”
Section: Discussionmentioning
confidence: 80%
“…Although TiO 2 scaffolds favor new bone ingrowth in vivo [6,8,11], in chronic bone defects the rate of bone growth was found to be too slow [12]. Therefore, bone tissue engineering (BTE) strategies are needed for these TiO 2 scaffolds to increase clinical translation.…”
Section: Introductionmentioning
confidence: 99%
“…Although some clinical studies have shown predictable bone gain, 1,2 others have reported less bone formation when using a graft material compared with when using the membrane alone. [3][4][5][6] In a previous in vivo experimental study, 7 GBR with a collagen membrane alone was compared with deproteinized bovine bone mineral (DBBM) and a ceramic TiO 2 scaffold. Less bone formation was observed in the TiO 2 and DBBM groups when compared with membrane alone group at the final follow-up time point after 12 weeks of healing.…”
Section: Introductionmentioning
confidence: 99%